2021
DOI: 10.3390/biomedicines9050546
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Gene Co-Expression Network Analysis Reveals Key Genes and Potential Drugs in Abdominal Aortic Aneurysm

Abstract: Abdominal aortic aneurysm (AAA) is a prevalent aortic disease that causes high mortality due to asymptomatic gradual expansion and sudden rupture. The underlying molecular mechanisms and effective pharmaceutical therapy for preventing AAA progression have not been fully identified. In this study, we identified the key modules and hub genes involved in AAA growth from the GSE17901 dataset in the Gene Expression Omnibus (GEO) database through the weighted gene co-expression network analysis (WGCNA). Key genes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The correlation between modules and sample traits was estimated so that modules that are highly correlated with sample traits could be identified and gene functions of related modules could be further studied. WGCNA significantly reduces errors caused by multiple testing problems inherent in microarray data, while maximizing the use of all data, as it uses all gene expression data from samples—instead of focusing only on differentially expressed genes—to construct the scale-free weighted network [ 35 ]. Furthermore, the scale-free weighted network has a high degree of robustness, which means that the errors in individual genes will not affect the overall results.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between modules and sample traits was estimated so that modules that are highly correlated with sample traits could be identified and gene functions of related modules could be further studied. WGCNA significantly reduces errors caused by multiple testing problems inherent in microarray data, while maximizing the use of all data, as it uses all gene expression data from samples—instead of focusing only on differentially expressed genes—to construct the scale-free weighted network [ 35 ]. Furthermore, the scale-free weighted network has a high degree of robustness, which means that the errors in individual genes will not affect the overall results.…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA is one of the most used methods for inferencing gene networks from transcriptomic data. Previous studies have used WGCNA to identify hub genes for AAA based on bulk transcriptomic data ( 19 , 20 ). But the same gene may have different effects on AAA progression in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Kan K.J. et al [6] further identified significant genes in abdominal AA patients. Moreover, the authors could predict the potential therapeutic compounds for these genes.…”
mentioning
confidence: 99%